Disinfection by-products In chlorinated drinking water and their potential health effects On humans: an international perspectives - Siti Fatinah Afiqah Sukiman (Penerbit Universiti Malaysia Perlis, 2011)
The use of chlorine as a disinfectant in drinking water has resulted to chemical compounds known as disinfection by-products (DBPs). The present of these compounds has become emerging issue due to its potential health effects on humans. To gauge the risk of DBPs on human health risk evaluation was carried out on selected compounds using cancer risk and probabilistic technique. 3-chloro-4-(dichloromethyl)-5-hydroxy-2(5H)- furanone (MX) and N-nitrosodimethylamine (NDMA) were selected based on their potential health effects on humans. Concentration data from several countries covering both compounds were gathered from published literature. More than 80% of the concentration data for MX and NDMA were below the WHO guidelines value of 6.7 ng/L and 100 ng/L respectively. The estimates human intake for MX and NDMA ranged between .610-9 to 1.310-5 mg/kg/day and 5.010-8 to 4.610-6 mg/kg/day respectively. With MX there is no overlap between exposure dose (EXPD) with Human Equivalent Dose (HED). The highest exposure dose was approximately 103 lower than the lowest HED value. However, with NDMA there is a high risk in the 80% population group with 1 in 10,000 is likely to obtain cancer associated with this exposure limit.